2018
DOI: 10.1101/277434
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of IRAK4 by microbial trimethylamine blunts metabolic inflammation and ameliorates glycemic control

Abstract: Referenced abstract The interaction between high-fat diet (HFD) feeding and the gut microbiome has a strong impact on the onset of insulin resistance (IR)1-3. In particular, bacterial lipopolysaccharides (LPS) and dietary fats trigger low-grade inflammation4 through activation of Toll-like receptor 4 (TLR4), a process called metabolic endotoxemia5. However, little is known about how the microbiome can mitigate this process. Here, we investigate longitudinal physiological and metabotypical responses of C57BL/6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Based on work done in mice [10,36], metabolic retroconversion of TMAO may be protective, and may even go some way to explaining why TMA and TMAO are detected at low levels in urine in the absence of dietary methylamines [17]. Chronic exposure of high-fat-fed mice to TMAO reduced diet-associated endoplasmic stress and adipogenesis, and improved glucose tolerance [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on work done in mice [10,36], metabolic retroconversion of TMAO may be protective, and may even go some way to explaining why TMA and TMAO are detected at low levels in urine in the absence of dietary methylamines [17]. Chronic exposure of high-fat-fed mice to TMAO reduced diet-associated endoplasmic stress and adipogenesis, and improved glucose tolerance [10].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic exposure of high-fat-fed mice to TMAO reduced diet-associated endoplasmic stress and adipogenesis, and improved glucose tolerance [10]. Exposure of high-fat-fed mice to TMA reduced low-grade inflammation and insulin resistance via inhibition of interleukin-1 receptor-associated kinase 4 (IRAK-4) [36]. Concentrations of the microbial signalling metabolite TMA used by Chilloux et al [36] were comparable to those found in normal human plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Described as a specific inhibitor of TMA production, DMB has been used in additional animal studies. 24,25 Unexpectedly, we found DMB did not reduce TMA production from choline by CutC in vitro or in E. coli . This result may be explained by the inability of DMB to engage in critical hydrogen bonding interactions within CutC’s polar active site.…”
mentioning
confidence: 62%
“…Teratomas were established for 24 days and confirmed through palpation prior to drug administration, which was given daily by oral gavage for 21 days at 15 mg/kg for both EDNRB-i and IRAK4-i. This dose was selected as a low-to-moderate dose based on previous animal studies (Chilloux et al, 2018;Serafim et al, 2015) and clinical trial of arthritis patients (ClinicalTrials.gov: NCT02996500). This treatment regimen was sublethal and did not interfere with recipient mouse health or overall body weight (Figure S5B).…”
Section: Validation Of Selective Targeting In Tri12 Cll Patient Cellsmentioning
confidence: 99%